2004
DOI: 10.1097/00042737-200402000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection in children from an urban community in north-east Brazil and risk factors for infection

Abstract: H. pylori is highly prevalent among children in a north-eastern Brazilian community characterised by poor living conditions, and this infection is largely acquired during early childhood. The infection increased with age, and domestic overcrowding. Further longitudinal studies must examine in depth the possible modes of transmission of the organism in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 18 publications
6
47
0
2
Order By: Relevance
“…In agreement with previously published data on the prevalence of H. pylori infection in the Portuguese population in paediatric age, 39% of the patients were H. pylori positive [12]. The presence of the infection was associated with older patients and, in keeping with previous studies, gender did not constitute a risk factor for H. pylori infection [13].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previously published data on the prevalence of H. pylori infection in the Portuguese population in paediatric age, 39% of the patients were H. pylori positive [12]. The presence of the infection was associated with older patients and, in keeping with previous studies, gender did not constitute a risk factor for H. pylori infection [13].…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with previous studies described by Goodman et al [38] and Xu et al [51] and are different from those observed in previous studies in Brazil, where no significant difference in the prevalence of the infection occurs among boys and girls [26,52]. In the present study, data were gathered from a general population of Japanese Brazilians with similar sociocultural levels and environmental conditions.…”
Section: Discussionsupporting
confidence: 85%
“…The results of the present study showed that the overall seroprevalence of H pylori infection was 46.6% in children at age 1-15 years and was 67.5% in adults at age 20-60 years. In different studies, the prevalence of H pylori is variable in children such that it has been reported to be 60% at age 4 years in Ethiopia [11] , 7.5% at age 2-18 years in Czech [12] , 44% at age 6 mo to 17 years in Turkey [13] , 8% at age 1-3 years in USA [14] , 50% at age 1-9 years and 80% at age 10-19 years in Libya [15] , 56% at age 1-14 years in Brazil [16] , 96% at age 1-14 years in Saudi Arbia [17] and 80% at age 1.5-5 years in Bangladesh [18] . Moreover, It has been reported that children in Gambia and Nigeria are almost all infected by H pylori at age of 5 years [19,20] .…”
Section: Discussionmentioning
confidence: 99%